Alat Bukti Tidak Langsung (Circumstantial Evidence) Dalam Perspektif Hukum Acara Pidana - Wicaksana, Satria Ardyrespati; Setyorini, Erny Herlin (Neolectura, 2024)
A judge in imposing criminal sanctions against a defendant will always use the provisions of Article 183 of the KUHAP as a guide. This provision essentially stipulates that the judge in sentencing must be based on a minimum of 2 (two) valid and convincing pieces of evidence that the defendant has committed a criminal act. In the provisions of Article 184 of the KUHAP, it regulates 5 (five) pieces of evidence, namely: a). Witness Statement; b). Expert Statement; c). Letter; d). Instruction; e). Defendant's statement. However, in the Central Jakarta District Court Decision Number: 777/Pid.B/2016/PN.Jkt.Pst, the judge used circumstantial evidence which is not regulated in the Criminal Procedure Code. In accordance with this description, the researcher is interested in conducting research with the title